MODULARISATION AS A COMPETITIVE CRITERION IN INDUSTRIES MANUFACTURING MACHINERY AND EQUIPMENT IN BRAZIL - Nunes, Fabiano de Lima; Antunes Júnior, José Antônio Valle; Dupont, André; Pires, Gabriel; Sordi, Jefferson Dobner; de Quevedo, Daniela Müller (The South African Journal of Industrial Engineering, 2020)
This research aimed at identifying the competitive criteria that, together with modularisation, impacted the differentiation strategy in industries manufacturing machinery and equipment in Brazil. This was survey-type research that used structural equation modelling (SEM-PLS) for data analysis. A total of 236 responses were obtained from participants in Brazilian machinery and equipment companies in the area of R&D, including directors, managers, coordinators, and supervisors. From this sample, the results show that applied modularisation positively impacted the competitive criteria related to innovation, quality, and flexibility, whereas, when applied to the delivery costs and performance criteria, it did not contribute to a competitive differential. Since it deals with a non-probabilistic sample by convenience, the present model does not represent the relationship between the constructs in a definitive way, for it concerns a model that address a sample of the machinery and equipment manufacturing industry, referring to ISIC D28, from Brazil.